การศึกษาการจัดโครงงานคณิตศาสตร์ในโรงเรียนประถมศึกษากรุงเทพมหานคร - วัฒนา เอี่ยวเส็ง (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objective of this research was to study the organization of mathematics projects in elementary schools, Bangkok Metropolis, in the aspects of preparation, implementation, evaluation and problems of mathematics projects. The subjects used in the research were 254 school administrators 127 teachers, and 36 students. The tools used in the research were a questionnaire, an interview form, an observation form and a document study form. The findings were as follows: 1. The projects preparation aspect: the administrators received the policy from the school; teachers received information through an explanatory meeting; teachers were sent to take a training course or attend a seminar; teachers and students provided tools and equipment; the school s budget was used; a reward was given to students in their honor. 2. The implementation aspect: most of mathematics projects were survey; the theme was selected according to the students interest and aptitude; teachers persuaded students to find the theme by asking questions; knowledge and skills in number were used in doing projects; a resource person or specialist was invited to participate in implementation; a senior class s project was introduced to students to see as an example; students worked on projects during lunch break; the work was monitored by requiring students to report periodically; the completed work was presented in front of the class. Teacher, students, friends and the students guardians were the project evaluators. 3. The evaluation aspect: project was evaluated by at the end of implementation and students were presented; the data obtained from the evaluation were used in the next plan adjustment. 4. Problems in doing projects : teachers lacked of skills in organizing mathematics projects; there was no supporting budget; students had inadequate knowledge about doing projects; student did not have enough time to do the projects; and students could not read fluently.